2016
DOI: 10.1186/s13068-016-0627-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and metabolomic analyses reveal metabolic responses to 3-hydroxypropionic acid synthesized internally in cyanobacterium Synechocystis sp. PCC 6803

Abstract: Background3-hydroxypropionic acid (3-HP) is an important platform chemical with a wide range of applications. In our previous study, the biosynthetic pathway of 3-HP was constructed and optimized in cyanobacterium Synechocystis sp. PCC 6803, which led to 3-HP production directly from CO2 at a level of 837.18 mg L−1 (348.8 mg/g dry cell weight). As the production and accumulation of 3-HP in cells affect cellular metabolism, a better understanding of cellular responses to 3-HP synthesized internally in Synechocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 83 publications
(140 reference statements)
0
23
0
Order By: Relevance
“…For complete details of protein extraction, digestion, labeling with iTRAQ reagents, LC–MS/MS analysis, and data analysis, please see the Additional file 1 : Additional methods section— iTRAQ-based proteomic analysis . Proteins displaying a 1.2-fold or more change between β-carotene producing strain YBX-01 and its parental strain YBX-B ( P < 0.05) were considered as differential expressed proteins [ 50 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…For complete details of protein extraction, digestion, labeling with iTRAQ reagents, LC–MS/MS analysis, and data analysis, please see the Additional file 1 : Additional methods section— iTRAQ-based proteomic analysis . Proteins displaying a 1.2-fold or more change between β-carotene producing strain YBX-01 and its parental strain YBX-B ( P < 0.05) were considered as differential expressed proteins [ 50 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…showed that overexpressing genes putatively involved in cobalt/nickel, manganese and phosphate transports could improve 3-HP production (Wang et al, 2016a).…”
Section: Optimizing 3-hp Production Through Metabolic Engineeringmentioning
confidence: 99%
“…Advances in high-throughput technologies such as proteomics, transcriptomics, and metabolomics are increasingly been used to understand how specific genes are expressed and the role they play in metabolic pathways associated with biofuel production by lignocellulose degrading microorganisms [ 230 , 231 ]. Computational tools are often used to obtain a mechanistic understanding of the information derived from these advanced technologies.…”
Section: Introductionmentioning
confidence: 99%